Tingkat Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) di Masyarakat Desa Betung Barat - Muslimin Muslimin; Ariska Juniarti; Agung Palendra; Siti Nurhikmah Pujiati; Mia Enjelina; Ikke Aulia Nabila; Susi Kurnianingsih; Febri Asti Hilda Zatira; Reli Yani; Muhammad Rizki; Mia Kaitana Helyanan; Novi Ernawati; Wulandari Wulandari; Rita Arieza (JURNAL PENGABDIAN KADER BANGSA, 2025)
This study aims to educate 1st to 3rd-grade students at SDN 3 Abab about the importance of Clean and Healthy Behavior (PHBS), particularly in washing hands correctly. The methods used include lectures, discussions, simulations, and monitoring the effectiveness of the program. The results show an improvement in the students' understanding of PHBS. Additionally, a survey in Betung Barat Village revealed that the majority of the community works as farmers with low incomes. Although basic infrastructure such as toilets is relatively adequate, 9% of households still lack proper sanitation. Adherence to posyandu activities is also low, with 56.7% of families regularly participating. This research uses a mixed-methods approach, combining qualitative and quantitative techniques to measure the impact of health education on community behavior. Overall, the study emphasizes the need for economic strengthening, improved access to healthcare, and optimization of maternal and child health services as steps to improve community welfare.